2021
DOI: 10.1259/bjr.20210417
|View full text |Cite
|
Sign up to set email alerts
|

Modern imaging of cholangitis

Abstract: Cholangitis refers to inflammation of the bile ducts with or without accompanying infection. When intermittent or persistent inflammation lasts six months or more, the condition is classified as chronic cholangitis. Otherwise, it is considered an acute cholangitis. Cholangitis can also be classified according to the inciting agent, e.g., complete mechanical obstruction, which is the leading cause of acute cholangitis, longstanding partial mechanical blockage, or immune-mediated bile duct obliteration damage th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 94 publications
0
8
0
Order By: Relevance
“…In patients with acute cholangitis, the pressure in the bile duct tends to be high. When the pressure in the bile duct rises to a certain level, the intercellular structure of the hepatocytes and the blood bile duct barrier may be destroyed, followed by patchy necrosis of hepatocytes, cholestasis and changes in liver function [21]. In this study, AST and ALP were found to be independent risk factors for developing acute cholangitis.…”
Section: ) T-bilmentioning
confidence: 52%
“…In patients with acute cholangitis, the pressure in the bile duct tends to be high. When the pressure in the bile duct rises to a certain level, the intercellular structure of the hepatocytes and the blood bile duct barrier may be destroyed, followed by patchy necrosis of hepatocytes, cholestasis and changes in liver function [21]. In this study, AST and ALP were found to be independent risk factors for developing acute cholangitis.…”
Section: ) T-bilmentioning
confidence: 52%
“…It is problematic that dynamic CT is required to obtain THAD findings, which is not a test that can be routinely performed in all centers and patients. Several findings regarding the plain magnetic resonance imaging (MRI) in AC (periportal abnormal intensity, high intensity in the liver parenchyma on T2 weighted images and so on) have been reported 24,25 . These MRI findings might be useful as an alternative for patients who cannot undergo dynamic CT; however, data regarding the MRI findings were not collected in the present study.…”
Section: Discussionmentioning
confidence: 80%
“…Several findings regarding the plain magnetic resonance imaging (MRI) in AC (periportal abnormal intensity, high intensity in the liver parenchyma on T2 weighted images and so on) have been reported. 24,25 These MRI findings might be useful as an alternative for patients who cannot undergo dynamic CT; however, data regarding the MRI findings were not collected in the present study. It is known that THAD occur in other conditions not associated with AC such as sepsis, 26 septic thrombophlebitis, 27 liver trauma including vascular injury, 28 arterial-portal shunt and portal venous stenosis, 29 so that THAD may not necessarily be specific to AC.…”
Section: Pbr-ac (Especially Those With Open Anastomosismentioning
confidence: 91%
“…Acute cholangitis (AC) occurs when biliary stenosis elevates pressure within the biliary system and causes spillover of bile and infection into the systemic circulation. 25,26 The Tokyo guidelines are useful for diagnosis (including imaging) and management of AC. 27 Ultrasound may show dilated biliary radicles and CBD and may also show the cause of obstruction.…”
Section: Acute Cholangitismentioning
confidence: 99%
“…Portal vein thrombosis may occur in patients with cholangitis. 25,26 Treatment consists of removal of cause of obstruction and/or biliary drainage along with appropriate antibiotic therapy (►Fig. 5).…”
Section: Acute Cholangitismentioning
confidence: 99%